Minimal Structural Requirements for Root Effect: The Crystal Structure of the Cathodic Hemoglobin Isolated from the Antarctic Fish Trematomus newnesi. - MAZZARELLA, LELIO; MERLINO, ANTONELLO; VERGARA, ALESSANDRO; G. BONOMI; M. LUBRANO; A. RICCIO; L. VITAGLIANO; C. VERDE; G. DI PRISCO (Proteins: Structure, Function, and Bioinformatics, 2006)
The cathodic hemoglobin component of the Antarctic fish Trematomus newnesi (HbCTn) is a Root-effect protein which displays peculiar features. The interpretation of its functional properties in relation to its sequence is puzzling. Indeed, HbCTn sequence is characterized by an extremely low histidyl content, and in particular by the lack of His146b and His69b, which are believed to be important in Bohr and Root effects, respectively. Furthermore, previous analyses suggested that the local environment of Asp95α, Asp99β, and Asp 101β should not be appropriate for the formation of Asp-Asp interactions which are important for the Root effect. Here we report the high-resolution crystal structure of the deoxy form of HbCTn. Our data provide a structural interpretation for the very low oxygen affinity of the protein and insights into the structural determinants of the Root effect. The structure demonstrates that the presence of Ile41α and Ser97α at the a1b2 interface does not prevent the formation of the inter-Asp interactions in HbCTn, as previous studies had suggested. The present data indicate that the hydrogen bond formed between Asp95α and Asp101β, which is stabilized by Asp99β, is per se sufficient to generate the Root effect, and it is the minimal structural requirement needed for the design of Root-effect Hbs.